The Chemical Stability Characterization and Kinetics of Statins in Aqueous Cyclodextrin Ocular Preparations: A Formulation Perspective - Ismael Abo Horan; Thorsteinn Loftsson; Hakon Hrafn Sigurdsson (Pharmaceutics, 2025)
Background: Topical statin therapy holds promise for ocular diseases, such as age-related macular degeneration, but the effective delivery to the posterior segment is limited by poor aqueous solubility, chemical instability, and ocular barriers. Cyclodextrins (CDs) can enhance statin solubility and stability; however, the behavior of CD–statin complexes in aqueous eye drops—particularly their influence on the equilibrium between the inactive lactone (ring closed) and active hydroxyacid forms (ring open)—remains unclear. This study aimed to (i) investigate how 5% and 10% (w/v) concentrations of selected CDs affect the lactone/acid equilibrium of simvastatin and atorvastatin and (ii) define formulation parameters (statin form, CD type and concentration, and pH range) for stable eye drop development. Methods: Simvastatin or atorvastatin was added to buffered solutions (pH 2.0 to pH 9.5) of RMβCD, HPβCD, γ-CD, or SBEβCD at 0%, 5%, and 10% (w/v), incubated at 23 ± 1 °C, and sampled over time for UPLC quantification of lactone and hydroxyacid forms, and rate constants for the forward and reverse reaction were calculated. Phase solubility studies were also conducted to further characterize equilibrium behavior in aqueous CD systems. Results: The lactone form was most stable at a pH of 4.5, while the hydroxyacid form prevailed at a pH ≥ 7. γ-CD and HPβCD accelerated lactone hydrolysis for both statins, whereas RMβCD exerted a stabilizing effect. Increasing the CD concentration from 5% to 10% provided minimal additional stabilization. Conclusions: These findings highlight that the precise control of the pH, an appropriate cyclodextrin choice, and the selection of the statin form are critical to developing chemically stable eye drops.